Temporal changes in hospital readmissions for postpartum hypertension in the US, 2010 to 2019; a serial cross-sectional analysis. - Ashwini Deshpande; Deepti Agnihotri; Alexa I K Campbell; Jerome J Federspiel; Evan R Myers; Osondu Ogbuoji (PLoS ONE)
Background Hypertension is the most common primary diagnosis associated with postpartum readmissions within 42 days of delivery hospitalization. In the United States, nearly half of the cases of eclampsia, a severe form of preeclampsia, develop during the postpartum period, and the postpartum onset of hypertensive disorders of pregnancy, like antepartum hypertension poses long-term health risks to pregnant individuals, including an increased likelihood of developing overall cardiovascular disease, coronary heart disease, heart failure, and chronic hypertension. In this paper, we estimate the trends in the incidence of readmissions for postpartum hypertension within 42 days of delivery discharge in the US, disaggregated by median household income. Methods and findings Using National Readmissions Database, we calculated the readmission rates for postpartum hypertension, both overall and stratified by ZIP Code median household income for each year between 2010 and 2019. We also calculated the percentage change and average annual growth rate (AAGR) in the rate of readmissions for postpartum hypertension between 2010 and 2019 for each income group. We then used a logistic regression model to compare the temporal changes in readmission for postpartum hypertension between the lowest and the highest income quartiles. The estimated incidence of postpartum hypertension readmissions doubled for all the income groups between 2010 and 2019 (0.36% vs. 0.8%). While the incidence of postpartum hypertension cases was higher among the lowest-income quartile, the increase in postpartum hypertension readmissions between 2010 and 2019 was greater in the highest-income quartile. Moreover, the incidence of postpartum hypertension readmissions rose faster in pregnant patients without a history of hypertension compared to those with a history of hypertension (AAGR 8.3% vs. 5.1%). Conclusion The increasing postpartum hypertension readmission burden suggests rising future health risks among mothers and a growing cost burden to the U.S. healthcare system. The higher rate of increase in postpartum hypertension readmissions among people without a history of hypertension calls for blood pressure checking in the postpartum period for all patients regardless of risk status.